1996
DOI: 10.1007/bf00333727
|View full text |Cite
|
Sign up to set email alerts
|

Rooting depth, water availability, and vegetation cover along an aridity gradient in Patagonia

Abstract: Above-and belowground biomass distribution, isotopic composition of soil and xylem water, and carbon isotope ratios were studied along an aridity gradient in Patagonia (44-45°S). Sites, ranging from those with Nothofagus forest with high annual rainfall (770 mm) to Nothofagus scrub (520 mm), Festuca (290 mm) and Stipa (160 mm) grasslands and into desert vegetation (125 mm), were chosen to test whether rooting depth compensates for low rainfall. Along this gradient, both mean above-and belowground biomass and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
206
3
24

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(250 citation statements)
references
References 15 publications
17
206
3
24
Order By: Relevance
“…Both types of adaptations could increase survival in such a dry and rather unfertile site (Grime 1979). Similarly, along an aridity gradient in Patagonia, Schulze et al (1996) found that plant total biomass decreased as precipitation decreased, but belowground biomass decreased at a lower rate than aboveground biomass, resulting in increasing root/shoot ratios. Fernández and Reynolds (2000) studying growth parameters and drought tolerance in eight desert grasses did not find a trade-off between total biomass or root/shoot ratios and drought tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…Both types of adaptations could increase survival in such a dry and rather unfertile site (Grime 1979). Similarly, along an aridity gradient in Patagonia, Schulze et al (1996) found that plant total biomass decreased as precipitation decreased, but belowground biomass decreased at a lower rate than aboveground biomass, resulting in increasing root/shoot ratios. Fernández and Reynolds (2000) studying growth parameters and drought tolerance in eight desert grasses did not find a trade-off between total biomass or root/shoot ratios and drought tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…With limited water, the quantity of water absorption is a function of root depth. Strong, deep roots can help the plants store and use the water kept in the soil efficiently [52].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding physiological responses of plants to environmental resource gradients is important for predicting spatial variation in ecosystem processes and for predicting ecosystem responses to climate change (Koch et al, 1995;Schulze et al, 1996). A strong rainfall gradient exists in northern Australia (Table 1 and Fig.…”
Section: Introductionmentioning
confidence: 99%